Membrane glucocorticoid receptors are localised in the extracellular matrix and signal through the MAPK pathway in mammalian skeletal muscle fibres. (14th May 2015) - Boncompagni, Simona; Arthurton, Lewis; Akujuru, Eugene; Pearson, Timothy; Steverding, Dietmar; Protasi, Feliciano; Mutungi, Gabriel
Abstract : Key points: Many studies have previously suggested the existence of stress hormone receptors on the cell membrane of many cell types, including skeletal muscle fibres; however, the exact localisation of these receptors and how they signal to the rest of the cell is poorly understood. In this study, we investigated the localisation and the mechanism(s) underlying the physiological functions of these receptors in mouse skeletal muscle cells. We found that the receptors were present throughout muscle development and that, in adult muscle fibres, they were localised in the extracellular matrix, satellite cells (muscle stem cells) and close to mitochondria. We also found that they signalled to the rest of the cell by activating enzymes called mitogen‐activated protein kinases. From these results we suggest that, at physiological concentrations, stress hormones may be important in skeletal muscle differentiation, repair and regeneration. Abstract: A number of studies have previously proposed the existence of glucocorticoid receptors on the plasma membrane of many cell types, including skeletal muscle fibres. However, their exact localisation and the cellular signalling pathway(s) they utilise to communicate with the rest of the cell are still poorly understood. In this study, we investigated the localisation and the mechanism(s) underlying the non‐genomic physiological functions of these receptors in mouse skeletal muscle cells. The results show that the receptors were localised in the cytoplasm in myoblasts, in the nucleus in myotubes, in the extracellular matrix, in satellite cells and in the proximity of mitochondria in adult muscle fibres. Also, they bound laminin in a glucocorticoid‐dependent manner. Treating small skeletal muscle fibre bundles with the synthetic glucocorticoid beclomethasone dipropionate increased the phosphorylation (= activation) of extracellular signal‐regulated kinases 1 and 2, c‐Jun N‐terminal kinase and p38 mitogen‐activated protein kinase. This occurred within 5 min and depended on the fibre type and the duration of the treatment. It was also abolished by the glucocorticoid receptor inhibitor, mifepristone, and a monoclonal antibody against the receptor. From these results we conclude that the non‐genomic/non‐canonical physiological functions of glucocorticoids, in adult skeletal muscle fibres, are mediated by a glucocorticoid receptor localised in the extracellular matrix, in satellite cells and close to mitochondria, and involve activation of the mitogen‐activated protein kinase pathway.